Effects of Aspirin on Myocardial Ischemia-Reperfusion Injury in Rats through STAT3 Signaling Pathway. (9th July 2021) - Wu, Zhenjun; Li, Xuewen; Li, Xiuyue; Yu, Lihua
Abstract : Objective . To investigate the role and mechanism of aspirin in myocardial injury induced by myocardial ischemia-reperfusion in rats through STAT3 signaling pathway. Methods . Sixty rats were randomly divided into three groups: the sham operation group, MI/R group, and MI/R+aspirin group (aspirin group). The rats in the sham operation group did not ligate the LAD coronary artery, while the aspirin group ligated the LAD coronary artery, which caused the suture to be loosened after 30 minutes ischemia, and 60 mg/kg aspirin was injected into the tail vein 10 minutes before reperfusion. After three hours of reperfusion, the ultrasound system was used to collect hemodynamic parameters, including ejection fraction (EF%), shortening fraction (FS%), and left ventricular end-systolic pressure (LVESP%) and left ventricular end-diastolic pressure (LVEDP%). Finally, the rats were euthanized; then, blood samples were taken for biochemical examination, myocardial tissue was collected, and the left ventricle was used for subsequent experiments. The gene expression levels of Bax and Bcl-2 were detected by PCR. The protein expression levels of Bcl-2, Bax, p-JAK2, total JAK2, p-STAT3, and total STAT3 were detected by Western blot. Results . Compared with the sham operation group and the aspirin group, the area of myocardial infarction in the MI/R was significantly increased (p < 0.05 ). In terms of hemodynamic parameters, LVEDP was significantly elevated in the MI/R group. The results of PCR showed that compared with the MI/R group, the mRNA expression of Bax in the aspirin group was significantly decreased, while that of Bcl-2 was significantly increased (p < 0.05 ). Western blot analysis showed that compared with the MI/R group, aspirin pretreatment significantly increased the expression levels of p-STAT3 and p-JAK2 (p < 0.05 ). Conclusion . The mechanism of aspirin preconditioning to protect the heart from MI/R injury appears to be related to JAK2/STAT3 and related to the activation of the signaling pathway.